Performance of European oysters (Ostrea edulis L.) in the Dutch North Sea, across five restoration pilots - Bos, Oscar G.; Duarte-Pedrosa, Stephanie; Didderen, Karin; Bergsma, Joost H.; Heye, Sonia; Kamermans, Pauline (Frontiers in Marine Science, 2023)
The European flat oyster (Ostrea edulis) is a biogenic reef former, internationally recognised as threatened and declining in the NE Atlantic by OSPAR and one of the focal species in nature inclusive designs in offshore windfarms in The Netherlands. European flat oyster reefs have disappeared from the Dutch North Sea in the early 1900s due to overfishing and diseases but are now subject of nature restoration. Since 2018, pilot projects have started in the Dutch North Sea to restore European flat oysters at suitable locations, such as offshore windfarms or natural reefs, which are protected from bottom trawling. We compared European flat oyster performance in five pilot projects, using translocated adult oysters sourced from Ireland, Norway, and the Netherlands. The aim of this research was to assess the performance of translocated oysters between pilots, to assess the installation and monitoring techniques, and to come forward with recommendations for future pilot projects. We found that translocation of both foreign sourced flat oyster populations (Ireland and Norway in nearshore and offshore areas) and local oysters (in nearshore areas) result in good oyster performance. Oysters were able to grow (max 3.67 mm/month) and reproduce (larvae present) in their new environment. We found that growth rate was explained by origin and average water temperature, to a lesser extent by number of months, location and salinity and not to other environmental factors such as pH and O2. Correlations between growth and environmental conditions need to be considered with caution, since not all pilots were sampled just before and after the growing season. Oysters were Bonamia-negative at the start and end of the pilots, indicating that the offshore Dutch North Sea is still Bonamia-free. By the year 2050 more than ten new offshore farms will be constructed in the Dutch North Sea and some sites will be suitable for oyster restoration. We conclude that local and foreign sourced oysters performed well at all locations. Based on the success and failure of the different outplacement and monitoring techniques, we provide recommendations on good practice for the future, including developing standardized monitoring protocols.